Influence of Methylenetetrahydrofolate Reductase C677T and A1298C Polymorphism on High-Dose Methotrexate-Related Toxicities in Pediatric Non-Hodgkin Lymphoma Patients - Lu, Suying; Zhu, Xiaoqin; Li, Wei; Chen, Huimou; Zhou, Dalei; Zhen, Zijun; Sun, Feifei; Huang, Junting; Zhu, Jia; Wang, Juan; Zhang, Yizhuo; Sun, Xiaofei (Frontiers in Oncology, 2021)
Purpose This retrospective study aimed to investigate the relationships between the methylenetetrahydrofolate reductase (MTHFR) C677T/A1298C and high-dose methotrexate (HD-MTX)-related toxicities in pediatric non-Hodgkin lymphoma (NHL) patients. Patients and Methods We reviewed the medical records of 93 NHL patients aged under 18 years who received HD-MTX therapy at the dose of 5 g/m2 with 24-h infusion at Sun Yat-sen University Cancer Center between 2014 and 2019. Results There were 61 males and 32 females, with a median age of 8.8 years (0.9–15.8 years). The tumor types included lymphoblastic lymphoma (n = 38), Burkitt’s lymphoma (n = 31), anaplastic large cell lymphoma (n = 18), diffuse large B-cell lymphoma (n = 6). Overall, 355 courses of HD-MTX therapy were prescribed. All patients were rescued with calcium folinate 12 h after the end of MTX infusion. We found that plasma MTX levels > 0.2 μmol/L at 48 h post-infusion increased the risk of developing oral mucositis (2.4% VS. 9.5%, P = 0.018). Also, patients carrying the C677T and T677T genotypes had tendencies to be more susceptible to oral mucositis (P = 0.034). Patients harboring mutant 677T allele were more likely to develop leucopenia (38.5 vs. 50.3%, P = 0.025) and thrombocytopenia (22.0 vs. 32.4%, P = 0.028). For polymorphism A1298C, the mutant genotype played a protective role in vomiting (11.1 vs. 4.3%, P = 0.018) but increased the risk of anemia (23.8 vs. 41.7%, P < 0.001) and leucopenia (38.1 vs. 50.3%, P = 0.021). Conclusion Childhood NHL patients harboring C677T genotype were more vulnerable to oral mucositis, leucopenia, and thrombocytopenia, while those with A1298C genotype were at a decreased risk of vomiting and more likely to develop anemia and leucopenia.